Agricultural biodiversity and women’s empowerment: a successful story from Kolli Hills, India - King, O.I.; Padulosi, S. (2017)
The Kolli Hills Agrobiodiversity Conservers' Federation (KHABCOFED) is a federation of successful entrepreneurs formally established in 2009 in Kolli Hills Taluk (Tamil Nadu, India) composed of 110 different groups and with a membership of 1,523 (985 men and 538 women). Millets play an important role in supporting agriculture in marginal areas which are increasingly stressed by climate change. The work of the Federation has contributed to improving the livelihoods of its members, especially women who showed active interest and participation within the research activities and training. It has also contributed to strengthening the conservation of millet diversity, making agriculture-based livelihood systems more resilient to climate change and improving access to nutritional foods.